Diagnostic Value of Sestrin2 in Patients with Obstructive Sleep Apnea - Chai, Jiagui (Metab Syndr Relat Disord, 2020)
Background: Obstructive sleep apnea (OSA) is a serious threat to individual health. Diagnosis of OSA is mainly polysomnography (PSG). However, PSG monitoring is costly and time-consuming. At present, increasing studies are exploring new diagnostic methods for OSA. This study aimed to explore the diagnostic role of Sestrin2 in OSA. Materials and Methods: Sixty-four subjects were recruited in this study. The concentration of plasma Sestrin2 of all subjects were measured and compared. Spearman's correlation analysis was used to investigate the correlation between plasma Sestrin2 concentration and other factors. Receiver-operating characteristic (ROC) curve was used to investigate the role of Sestrin2 in the diagnosis of OSA, moderate-severe and severe OSA. Results: Subjects were divided into OSA group (n = 38) and control (n = 26). Levels of Plasma Sestrin2 were significantly higher in OSA patients than in controls. Sestrin2 was positively correlated with oxygen reduction index and negatively correlated with mean oxygen saturation and lowest oxygen saturation. The area under ROC curve (AUC) of Sestrin2 for OSA diagnosis was 0.740 [95% confidence interval (CI), 0.615–0.842], the cutoff value was 1.86 ng/mL, and the sensitivity and specificity were 81.58% and 61.54%, respectively. The AUC of Sestrin2 for the diagnosis of severe OSA was 0.801 (95% CI, 0.682–0.890), and the cutoff value was 5.21 ng/mL exhibiting the sensitivity and specificity of 61.90% and 90.70%, respectively. Conclusion: Setrin2 is a marker for OSA and may be helpful in the diagnosis of OSA.